Dynamical systems approach to theoretical models of disease s: Application to nonlinear HIV dynamics and blood vessel flows with aneurysm - Moreira, Lorena de Sousa (2020)
Dissertação (Mestrado em Engenharia Biomédica) – Universidade de Brasília, Faculdade UnB Gama, Programa de Pós-Graduação em Engenharia Biomédica, 2020.